Electrical properties of vertical GaN Schottky diodes on Ammono-GaN substrate. (15th June 2019) - Kruszewski, P.; Prystawko, P.; Grabowski, M.; Sochacki, T.; Sidor, A.; Bockowski, M.; Jasinski, J.; Lukasiak, L.; Kisiel, R.; Leszczynski, M.
Abstract: We report on electrical properties of vertical n-GaN high voltage Schottky diodes (SBDs) grown by two different techniques: Metal Organic Chemical Vapor Deposition (MOCVD) and Hydride Vapor Phase Epitaxy (HVPE) on highly-conductive n-type Ammono-GaN substrate. The thermionic emission (TE) current model has been applied for diodes parameters analysis. The fabricated SBDs exhibited a breakdown voltage of 670 V and 220 V, barrier height of 1.05 eV and 0.92 eV, ideality factor of 1.65 and 1.42 and series resistance of 440 Ω and 12 Ω for HVPE and MOCVD samples, respectively. Finally, we demonstrate preliminary point defects analysis for both types of the samples.